A SERS pH sensor for highly alkaline conditions and its application for pH sensing in aerosol droplets. Issue 19 (5th May 2022) - Liu, Boyu; Huang, Yuting; Zheng, Wenxu; Wang, Dongmei; Fan, Meikun
Abstract : A SERS pH sensor employing Alizarin Yellow R as the molecular probe was developed for use in strong alkaline solutions. Abstract : Surface-Enhanced Raman Scattering (SERS) has been widely used in pH sensing. However, SERS sensors capable of stably analysing pH under highly alkaline conditions are still scarce. In this work, a SERS pH sensor employing Alizarin Yellow R as the molecular probe was carefully developed for strong alkaline solutions. The results showed that the probe presented excellent sensing performance in the pH range of 10.04–14.04, including desirable stability and reversibility. Raman band assignments of the probe molecules with the protonated and deprotonated forms were calculated using Gaussian 09. To demonstrate the application, we measured the centroid pH of the phosphate buffer (PB) droplet and compared it to the value obtained with 4-mercaptobenzoic acid (4-MBA) as a probe.